Ultrasound-guided intra-muscular botulinum toxin A in athletes with chronic adductor-related groin-pain: A retrospective observational study - Julien Orhan; Romain Garofoli; Émilie Alperin; Fabien Ladauge; Jennifer Zauderer; Guillaume Paris; François Rannou; Christelle Nguyen; Marie-Martine Lefèvre-Colau (JSAMS Plus)
Introduction: Chronic adductor-related groin pain (AP) is a frequent and disabling sport condition. Intra-muscular injection of botulinum toxin A may have positive effects on pain in some chronic tendinitis. We aimed to describe the short-term evolution of pain, activity limitations and quality of life, after an injection of the adductor longus with botulinum toxin A, as an add-on therapy to standard of care in patients with chronic AP. Method: We conducted a retrospective observational single-centered study. We included individuals with clinical and MRI chronic AP, for whom medical and/or surgical treatments have failed and who were treated with an intra-muscular injection of botulinum toxin A (100 units of botulinum toxin A in the adductor longus) under ultrasound guidance. Participants were assessed 50 days after injection for pain using a numerical rating scale (NRS) and for activity limitations and quality of life using the Copenhagen Hip and Groin Outcome Score (HAGOS). Participants were also asked to self-report adverse events. Results: We included 20 participants. Mean age was 34.3 (11.7) years and mean symptom duration was 48.9 (61.6) months. Mean pain decreased from 55.3 (SD [22.4] before injection to 38.3 [21.7], 50 days after injection (p ​= ​0.027). Each of the 6 HAGOS subscales improved before and after injection. No serious adverse events were self-reported by the patients included in the main analysis. Conclusion: In this retrospective uncontrolled trial, we observed a numerical decrease in pain intensity in individuals with chronic AP 50 days after intra-muscular botulinum toxin A injection in the adductor longus.